Passengers preference and satisfaction of public transport in Malaysia - Ismail, Rozmi; Hafezi, Mohammad Hesam; Mohd Nor, Rahim; Ambak, Kamarudin (AENSI Publishing Corporation, 2012)
Nowadays, Malaysia facing with an explosive growth in vehicle ownership and utilization, which led to traffic congestion and pollution. In this situation, government policy encourages people to use public transportation. However, Malaysia are prefer to use private vehicle become many reasons including bad quality of services. In this regard, public transport operators are forced to place emphasis on the monitoring and improvements of the services provided. This study focuses on traveler’s satisfaction and preference towards public transport with service quality attributes. Self rate questionnaire was used to investigate overall customer satisfaction and factor that influence public transport users’ satisfaction. A survey was conducted on an actual public transportation network in Kuala Lumpur, Malaysia. The aim was to evaluate the parameters in passenger preference and satisfaction on public transportation network using statistical model included variable such as facilities, comfortness and quality of services. Data were analyzed using descriptive, correlation, factor and multiple regression analysis. Result show that influences of satisfaction parameters are more than preference parameters. The application of this study suggest that the public transport operation especially buses must improve their quality of services to the prospect passengers.